2014
DOI: 10.1177/0022022114563612
|View full text |Cite
|
Sign up to set email alerts
|

Improving Research in the Emerging Field of Cross-Cultural Sociogenetics

Abstract: We offer a critical overview of studies associating genetic differences in the 5-HTTLPR VNTR in the serotonin-transporter gene with societal differences. We also highlight recent findings from individual-level research on 5-HTTLPR generating new hypotheses concerning the effect of genes on culture. We provide an expanded national index reflecting 5-HTTLPR S-allele prevalence as an improved tool for future research. Our preliminary tests of this tool suggest that national S-allele prevalence is not associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…We found that the genotype frequencies in the larger Asian sample significantly differed from the Caucasian sample from the previous study (Marsh et al ., 2011). According to a cross-cultural psychological study showing that cultural variation may be a result of gene-brain interplay (Minkov et al ., 2015), the prevalence of the 5-HTTLPR among races may underpin the ethnic and cultural differences in moral behaviors (Baartman et al ., 1999; Moon, 1986). Thus, the new findings extend our understanding of the genetic basis of moral judgment.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the genotype frequencies in the larger Asian sample significantly differed from the Caucasian sample from the previous study (Marsh et al ., 2011). According to a cross-cultural psychological study showing that cultural variation may be a result of gene-brain interplay (Minkov et al ., 2015), the prevalence of the 5-HTTLPR among races may underpin the ethnic and cultural differences in moral behaviors (Baartman et al ., 1999; Moon, 1986). Thus, the new findings extend our understanding of the genetic basis of moral judgment.…”
Section: Discussionmentioning
confidence: 99%
“…For further review of the history and development of the study of culture, readers may also be interested in several related literature reviews (Erez and Gati 2004;Taras et al 2009Taras et al , 2010Sullivan and Cottone 2010;Dickson et al 2012;Shockley et al 2017), meta-analyses (Panda and Gupta 2004;Boer and Fischer 2013), historical overviews (Berry et al 1997), and a range of studies (e.g., Esmer and Pettersson 2007;Gelfand et al 2006;Gibbs et al 2007;Miller 2002Miller , 2005Minkov 2008;Minkov and Blagoev 2009;Minkov et al 2015;Miyamoto 2013;Owe et al 2013;Sarala and Vaara 2010;Schimmack et al 2005;Franke and Richey 2010;Shao et al 2010;Stankov 2011;Stankov and Lee 2008;Stankov et al 2014;Stephan and Uhlaner 2010;Toh and Leonardelli 2012;Thalmayer and Saucier 2014;Vignoles et al 2018;Yates et al 2010;Yu 2015;Zou et al 2009). In addition, these journal special issues include articles with more information: (1) The Value of Values in Cross-cultural Research in the Journal of Cross-cultural Psychology (2011; volume 42, issue 4); and (2) Cross-cultural value mismatch in the International Journal of Psychology (e.g., Aumann and Titzmann 2018;Bossong and Keller 2018;Wu et al 2018;Greenfield 2018;Glazer et al 2018).…”
Section: History Of Cross-cultural Studiesmentioning
confidence: 99%
“…The burgeoning literature on gene–environment interactions establishes with increasing clarity that trait-encoding genes distribute in different frequencies across populations and might explain country-level differences in the distribution of psychological traits. Minkov, Blagoev, and Bond (2014) cite various studies that show an individual-level link between the short-allele polymorphism of the serotonin transporter gene 5-HTTLPR and risk aversion. In addition, these authors present a strong cross-national correlation between the demographic prevalence of the short-allele polymorphism and “hypometria,” of which risk aversion is a central component.…”
Section: Conceptual Frameworkmentioning
confidence: 99%